Cost of industrial product-service systems (IPS2) - Roy, Rajkumar; Datta, Partha Priya; Romero Rojo, Francisco Javier; Erkoyuncu, John Ahmet (CIRP, 2009)
The motivation of this Keynote comes from the lack of research in estimating costs of an industrial product-service system (IPS2 ). A competitive IPS2 framework has been developed by Cranfield University for delivering sustainable customer value. This framework describes the capabilities of solution providers and the constraints involved in delivering IPS2 . The paper builds on this framework by considering cost at various stages of the life cycle. The framework will analyse the key drivers, the major issues and how the cost evolves from traditional pure product perspective to IPS2 from the point of view of the customer and the solution provider. The obsolescence, uncertainty, supply chain and customer value areas are analysed in-depth because they are found to be the major drivers in IPS2.
Keywords: Industrial product-service systems; cost; uncertainty; obsolescence; supply chain